Evaluating Environmental, Social and Governance (ESG) Practice Among Malaysian Public Listed Construction Companies Using FTSE Russell Rating Model - Sulaiman, Nurul Nabila; Omar, Abdul Jalil; Pakir , Faizal; Mohamad, Marlina (International Journal of Sustainable Construction Engineering and Technology, 2024)
Implementation of Environmental, Social and Governance (ESG) in company strategy has become critical as it increases investors confident in the company. A company without ESG strategies will have problem on loss of intellectual capital, loss of customers, sales and decline in reputation. Failed to disclose ESG information perceived as having poor investments in high-risk sectors. Therefore, the purpose of this paper is to evaluate current ESG practices disclosed in annual reports and sustainability statements among 55 construction sector companies listed in Bursa Malaysia from 2021 until 2022. The investigation was conducted using content analysis based on ESG pillars and themes of FTSE Russell rating model. The rating model consists of 3 individual pillars and 14 themes. A binary scoring method was used, and the result was analyses in descriptive analysis. Based on the content analysis, the results indicate that social pillar has the highest percentage of ESG practice among the construction company with 64% score with the focus on health & safety. Environmental pillar practice remains the second highest score with 57.45% followed by governance with 55% score. The findings of this study are useful to investors, government agencies such as Bursa Malaysia and Securities Commission, industry, policy makers, and other related agencies. This study is among the first content analysis study on auditing ESG practices of construction sector in Malaysian public listed companies guided by FTSE Russell rating model.